A rapid assessment of the political economy of health at district level, with a focus on maternal, newborn and child health, in Bangladesh, Indonesia, Nepal and the Philippines. Issue 10 (11th October 2019) - Hipgrave, David B; Anderson, Ian; Sato, Midori
Abstract: Low- and middle-income countries (LMICs) face many challenges and competing demands in the health sector, including maternal and newborn mortality. The allocation of financial and human resources for maximum health impact is important for social and economic development. Governments must prioritize carefully and allocate scarce resources to maximum effect, but also in ways that are politically acceptable, financially and institutionally feasible, and sustainable. Political economy analysis (PEA)—that gets what, when and why—can help explain that prioritization process. We used PEA to investigate how four Asian LMICs (Bangladesh, Indonesia, Nepal and the Philippines) allocate and utilize resources for maternal, newborn and child health (MNCH). Using mixed research methods including a literature review, field interviews at national and sub-national level, and policy, process and budget analysis in each country, we examined three political economy issues: (1) do these countries demonstrably prioritize MNCH at policy level; (2) if so, is this reflected in the allocation of financial and other resources and (3) if resources are allocated to MNCH, do they achieve the intended outputs and outcomes through actual programme implementation? We also considered the influence of transnational developments. We found that all four countries demonstrate political commitment to health, including MNCH. However, the health sector receives comparatively low public financing, governments often do not follow through on plans or pronouncements, and capacity for related action varies widely. Poor governance and decentralization, lack of data for monitoring and evaluation of progress, and weak public sector human resource capacity were frequent problems; engagement of the private or non-government sectors is an important consideration. Opportunities exist to greatly improve equity and MNCH outcomes in these nations, using a mix of evidence, improved governance, social engagement and the media to influence decisions, increase resource allocation to and improve accountability in the health sector.